NGHIÊN CỨU NẤM MEN PHÂN LẬP TỪ XỐP POLYESTE POLYURETHAN TRONG THÙNG NHIÊN LIỆU MÁY BAY SU-30 MK2 Ở SÂN BAY BIÊN HÒA - Nguyễn, Thu Hoài; Đỗ, Tất Thịnh; Lê, Ngọc Minh; Vũ, Xuân Nam; Phạm, Thị Thu Huyền (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
STUDY ON YEASTS ISOLATED FROM POLYESTE POLYURETHANE FOAM USED IN SU-30 MK2 AIRCRAFT’S FUEL TANK AT BIEN HOA AIRPORTIn the present study, six strains of yeast were isolated from the broken PPU foam, which has been used in Su-30 MK2 aircraft for 6 years at Bien Hoa airport. Strain BHH3 was determined as a yeast candidate capable of producing polyurethanase and urease to break down PPU. In liquid mineral medium supplemented with PPU as the only carbon and energy sources, the strain BHH3 grew and attached to the PPU foam surface, and changed its colour from light yellow to brown just after 7 days at 30°C. After 28 days testing, the tensile strength and elongation at break in the PPU foam was reduced significantly, reaching 11.8N/m2 and 249%, in comparison with that of the control of 12.6 N/m2 and 335%, respectively.